Problematika Dalam Implementasi Model Cooperative Learning STAD Terhadap Pembelejaran Maharah Qiro'ah bahasa arab - Ilal, Muhammad Nuzulullail Mifta; Hakami, Fauzan; Rohman, Subhan Khoirir; Nabil, Muaz Kalimatun (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
This research examines how problematic the model is STAD in learning Reading skills and strategies for overcoming obstacles in implementation STAD. This approach uses a qualitative approach with the aim of synthesizing theory tests and case studies that have been done by previous research and practitioners on the model STAD in learning reading skills. By taking several studies that are relevant to implementation sub-research STAD in learning Reading skills This research uses a systematic literature review (SLR) method. The data sources for this research come from a number of journal articles, main documents, and supporting documents. The results of this research identify problems and how to overcome them in implementing the model STAD to learning Reading skills. Research as a way to overcome model problems STAD This includes what obstacles there are in teaching and learning activities, and the results of how to overcome this STAD model in learning Reading skills. The impact of this research creates a strategy to be recommended in teaching and learning activities between students and teachers and can provide a new color to learning reading skills with models STAD.